Interactive E-Modules for Arts Education: Improving Comprehension and Engagement in Nusantara Music Courses - Ayuthia Mayang Sari; Robby Ferdian; Olan Yogha Pratama; Novita Efendi; Belirda Wulan Dhari (Jurnal Edutech Undiksha, 2024)
The use of teaching modules in learning processes still faces challenges, especially printed materials that tend to be monotonous and less appealing to students in the digital era. These challenges affect students' understanding and engagement in learning, particularly in courses that require artistic appreciation, such as Nusantara Music. This study aims to analyze the effectiveness of developing interactive e-modules to enhance students' comprehension and engagement in this course. The research employed a research and development (R&D) method using the ADDIE development model, which comprises five stages: Analysis, Design, Development, Implementation, and Evaluation. Data were collected through pretests and post-tests to measure cognitive and psychomotor learning outcomes. Data analysis was conducted by comparing pretest and post-test results using descriptive statistical tests. The findings revealed that the developed interactive e-module effectively improved students' comprehension, as indicated by significant improvements in post-test scores compared to pretest scores. Additionally, the use of e-modules increased student engagement during the learning process. The study concludes that the ADDIE-based interactive e-module can be effectively utilized as a learning medium to enhance students' learning outcomes in the Nusantara Music course.